STRATEGI PENINGKATAN LITERASI KEBENCANAAN DENGAN PENDEKATAN SAINS DAN TEKNOLOGI MASYARAKAT BAGI SISWA SEKOLAH DASAR DI WILAYAH PESISIR KOTA BENGKULU - Dyah Setyo Rini; Herlin Fransiska; Nutia Rosdalena; Reyvo Valeriyan; Eko Heru Purwanto; M. Taufiqurrahman Syah; Elfi Yuliza (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
As the capital of Bengkulu Province, Bengkulu City is located not far from the coast, so most community activities are also located around the coastal area, including schools, both elementary and high schools. Bengkulu City is prone to earthquakes and tsunamis, so disaster preparedness is very needed from an early age through earthquake and tsunami disaster literacy training in order to reduce the impact of these disasters. This community service activity carries the theme of disaster literacy using the application of science and technology, including the creation of interesting animated videos, the use of drones for making evacuation route maps, and pocketbooks that are easily understood by students of SD Negeri 2 Bengkulu City. Based on the results of the paired data t-test for evaluation used to pretest and posttest scores, it was found that the earthquake and tsunami disaster literacy training had a significant effect on the knowledge and understanding of third-grade students of SDN 2 Bengkulu City.